KETIMPANGAN PERAN GENDER DALAM PENGASUHAN ANAK DAN KAITANNYA DENGAN STUNTING (Studi Kasus Pada Keluarga Yang Memiliki Balita Stunting Di Desa Plumbon Tahun 2024) - Widiyanti, Ike; Rudiansyah, Rudiansyah (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2024)
Patriarchal culture remains a persistent phenomenon in families in Plumbon Village, contributing to the high prevalence of stunting in toddlers. This study aims to describe the patterns of patriarchal behavior in families with stunted children. A descriptive qualitative design was employed, utilizing in-depth interviews with seven families having stunted toddlers. The results revealed that in patriarchal families, men primarily act as breadwinners, while women bear full responsibility for childcare and nutritional fulfillment. The low involvement of fathers in parenting and the limited access of mothers to economic resources and health information are key factors contributing to stunting. Additionally, interviews with village officials confirmed that patriarchal culture is still prevalent in the community, reinforcing parenting patterns that do not optimally support child development. Therefore, gender-based interventions that actively engage fathers in childcare and provide education to families are essential to promote a more inclusive parenting approach and prevent stunting.